Cytotoxic Activity of Flavonoid Compounds Isolated from Tetrameles Nudliflora Leaves - Megawati, Megawati; Darmawan, Akhmad; Fajriah, Sofa (BRIN, 2019)
Tetrameles nudliflora is one of the endemic plants in Wallace region, especially in Mekongga Forest, Southeast Sulawesi, Indonesia. As part of our project in the field of natural drug discovery based on local bioresources, this study aimed to isolate secondary metabolite compounds from the ethyl acetate fractions of the leaves of T. nudiflora and evaluate their cytotoxic activities against breast carcinoma cancer lines, MCF-7. The methods used were various chromatography techniques such as vacuum column chromatography, gravitation column chromatography, thin layer chromatography, preparative thin layer chromatography, and re-crystallization using two different organic solvents. In the present study, two flavonoid compounds, kaempferol (1) and quercetin (2) were identified. The structures of 1-2 were determined using serial spectroscopic techniques, including mass spectrometry, one- and two-dimensional nuclear magnetic resonance. Moreover, using 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide (MTT) assay method, both compounds showed in vitro cytotoxic activity IC50 of 34.162 and 133.148 μg mL-1, respectively against MCF-7 cell lines.